Quality of life among hepatitis C patients on treatment, Minia, Egypt - Kamal, Nashwa N.; Mahfouz, Eman M.; Ewis, Ashraf A.; Refaei, Sara A.; Soliman, Wael A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Hepatitis C is a highly prevalent infectious disease among Egyptian population. Different types of interferon and antiviral drugs are used in the treatment and have significant side effects which may alter quality of life of the treated chronic hepatitis C patients. The aim of the study was to identify the course of and factors associated with HRQOL in HCV patients given standard treatment based and to assess its relation to socio-demographic and clinical characteristics. Methods: This prospective consecutive hospital based study included 120 chronic hepatitis C patients in El-Minia city and by using SF-36V2 questionnaire. Results: HRQOL baseline scores, general health had the lowest score, followed by vitality, while Role emotional had the highest score. Physical component summery scores (PCS) was slightly higher than mental component summery scores (MCS) for PCS. Subjects showed significantly lower SF-36 scores at the 12th week of treatment Compared to the pretreatment values. Mean scores of all SF-36 domains improved by the end of treatment, (p<0.01). Scales most affected during therapy were vitality (VT), general health (GH) and bodily pain (BP). The effect size (ES) observed on SF-36 subscales, the most affected dimensions at the 12th week of treatment were (PF, SF, VT and BP) (they were ≥0.8) could be considered large change, according to Cohen’s criteria. Conclusions: Subjects showed significantly lower SF-36 scores at the 12th week of treatment. Mean scores of all SF-36 domains improved by the end of treatment.